Sonolytic Oxidation of Tc(IV)O2nH2O Nanoparticles to Tc(VII)O4 in Aqueous Solution - M. Zakir; T. Sekine (Atom Indonesia, 2010)
Sonolysis of a hydrosol of TcO2nH2O was investigated in the Ar- or He- atmosphere. Colloidal TcO2nH2O nanoparticles were irradiated with a 200 kHz and 1.25 W/cm2 ultrasound. It was found that the TcO2nH2O colloids dispersed in an aqueous solution (under Ar or He atmosphere) was completely dissolved by ultrasonic irradiation (200 kHz, 200 W). The original brownish black color of the suspension slowly disappeared leaving behind a colorless solution. This change suggests that oxidation of Tc(IV) to Tc(VII) takes place. The oxidation was almost complete during 30 minutes sonication time under argon atmosphere for initial concentration of 6.0E-5 M. Addition of t-butyl alcohol, an effective radical scavenger which readily reacts with OH radicals, supressed the dissolution of TcO2nH2O colloids. This reaction indicates that TcO2nH2O molecules are oxidized by OH radicals produced in cavitation bubbles. Received: 20 November 2009; Revised:14 April 2010; Accepted: 18 April 2010